A REVIEW ON ROLE OF ANTIOXIDANTS IN DIABETES - Rajendiran, Deepa; Packirisamy, Subbulakshmi; Gunasekaran, Krishnamoorthy (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Diabetes mellitus is a chronic metabolic disease. Oxidative stress plays a major part in the pathogenesis of diabetes. Supplementation with antioxidants and the medicinal plants which possess antioxidants activity have been reported their hypoglycemic activity. The antioxidants are used to treat and reduce the complication of diabetes mellitus. The diet supplementations of antioxidants vitamins are beneficial in the treatment of diabetes. This review article was summarizing the role of antioxidants in diabetes mellitus.